L’insegnante e lo Stress - Carraro, Maria Cristina; Cifiello, Stefano (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
First of all will be presented some minimal results taken from the huge literature on the subject, with reference to Stress and consequent Burn Out phenomena, then will be illustrated what is deduced from the mentioned literature on the specific topic of the Teacher’s stress. Again will be provided some methodological addresses for relieving work stress in general, but useful with reference to Teachers then to illustrate the partecipatory research carried out with the World Cafè methodology, which will be shortly provided the operational features. Finally will be presented the way of stress manifest among the Teachers as it comes from the research, in order to propose a possible stress intervention procedure.